TELEVISI LOKAL: MEDIA KEBANGKITAN SENI PERTUNJUKAN TRADISIONAL DI ERA GLOBALISASI MEDIA - Renta Vulkanita Hasan (LITERASI: Indonesian Journal of Humanities, 2014)
Mass media such as television, it can simply be defined as one of the instruments which reinforce efforts in the realization of human-related obsessions certain aspects, such as art. The art form of indigenous territories, such as performing arts and cultural image representation of complex societies, especially the creative process in the art community. The results are reflected in the creative community is a form of performing art that is inseparable from the process dependence, experiences shared, and collaboration among members of the various communities. The process that takes place at the level of larger, complex, and increasingly not much hampered by physical barriers to be the reason that the traditional performing arts worthy of competing and widely publicized. Local television is a means of publicity and promotion of traditional performing arts, the most effective given the role on television today have massive strength in delivering a variety of impressions to the community. This study is a follow-up, which has the form of the model output shows the traditional performing arts in a television documentary format. Documentary television is a format appropriate to revive the “breath” of traditional performing arts in the area of media globalization. Keywords: globalization, media, performing arts, local television